1987
DOI: 10.1083/jcb.104.6.1611
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, heterologous down-regulation of the epidermal growth factor receptor in PC12 cells by nerve growth factor.

Abstract: Abstract. Cells of the rat pheochromocytoma clone PC12 possess receptors for both nerve growth factor (NGF) and epidermal growth factor (EGF), thus enabling the study of the interaction of these receptors in the regulation of proliferation and differentiation. Treatment of the cells with NGF induces a progressive and nearly total decrease in the specific binding of EGF beginning after 12 h and completed within 4 d. Three different measures of receptor show that the decreased binding capacity represents, in fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
38
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…It was of interest to determine what would happen if the cells were exposed to both stimuli at the same time. The answer was that the cells simply did not respond to EGF after they had been treated with NGF, and the reason that they did not respond is that the EGFR is markedly down-regulated by treatment of the cells with NGF (3).…”
mentioning
confidence: 99%
“…It was of interest to determine what would happen if the cells were exposed to both stimuli at the same time. The answer was that the cells simply did not respond to EGF after they had been treated with NGF, and the reason that they did not respond is that the EGFR is markedly down-regulated by treatment of the cells with NGF (3).…”
mentioning
confidence: 99%
“…PC12 cells treated with NGF exhibit an attenuated response to EGF (9) because EGF receptors are down-regulated (9,11). The cellular mechanisms that mediate NGF-induced EGF receptor down-regulation are unknown and represent an interesting question in neuronal development.…”
mentioning
confidence: 99%
“…Cell Culture-PC12 cells were grown in Dulbecco's modified Eagle's medium (DMEM; Life Technologies, Inc.) supplemented with 7% fetal bovine serum, 7% horse serum, 100 g/ml streptomycin, and 100 units/ml penicillin, all from Life Technologies, Inc. (11). In all experiments involving extended treatment with NGF, the medium was changed, and fresh NGF was added every other day.…”
mentioning
confidence: 99%
“…NGF-induced down-regulation of the EGFR is under transcriptional control (17), and that control is p140trk-, Ras-, and Src-dependent (16). The detailed cellular and molecular mechanisms that mediate NGF-induced EGFR down-regulation are unknown.…”
mentioning
confidence: 99%
“…Our previous studies (16,17) have shown that treatment of PC12 cells with NGF causes a profound down-regulation of both EGFR mRNA and protein. NGF-induced down-regulation of the EGFR is under transcriptional control (17), and that control is p140trk-, Ras-, and Src-dependent (16).…”
mentioning
confidence: 99%